2018
DOI: 10.1029/2017wr022279
|View full text |Cite
|
Sign up to set email alerts
|

Nonstationary Hydrologic Behavior in Forested Watersheds Is Mediated by Climate‐Induced Changes in Growing Season Length and Subsequent Vegetation Growth

Abstract: Forested watersheds provide important ecosystem services through the provision of high quality freshwater, mitigation of floods, and maintenance of base flows. How alteration of these services under ongoing climate change is mediated by vegetation dynamics is not fully understood. Combining independent remote sensing based vegetation information and distributed hydrological modeling, we investigated the impact of climate‐induced vegetation dynamics on long‐term non‐stationary hydrologic behavior in two foreste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 78 publications
(108 reference statements)
3
60
0
Order By: Relevance
“…Because our analysis focused on HCDN catchments, we assumed that catchment properties (parameter n) do not change in the future, thereby setting the n sensitivity coefficient and dn to 0. We recognize that this assumption is likely an oversimplification of future landscape conditions, particularly in light of changes in forest structure, age, productivity, and growing season length [32,68,69] in relatively undisturbed catchments throughout the region. Future analysis should consider dn to more thoroughly account for ecosystem changes important to the partition of P into E and Q.…”
Section: Modeling Future Streamflowmentioning
confidence: 99%
See 1 more Smart Citation
“…Because our analysis focused on HCDN catchments, we assumed that catchment properties (parameter n) do not change in the future, thereby setting the n sensitivity coefficient and dn to 0. We recognize that this assumption is likely an oversimplification of future landscape conditions, particularly in light of changes in forest structure, age, productivity, and growing season length [32,68,69] in relatively undisturbed catchments throughout the region. Future analysis should consider dn to more thoroughly account for ecosystem changes important to the partition of P into E and Q.…”
Section: Modeling Future Streamflowmentioning
confidence: 99%
“…Since 1951, the monthly Q throughout the region has increased by 1 to 2 mm/year, with the largest increases during the fall and winter seasons due to increases in precipitation [29]. Coincidentally, the forest growing season length throughout the region has increased on average by 22 days since 1983 [30] as has E, which has increased between 0.4 to 4 mm/year [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated that incorporation of dynamic vegetation phenology in ecohydrologic models improves streamflow (Kim et al, 2018) and vegetation water use/growth (Hwang et al, ) predictions. Our study shows that inter‐annual variability of vegetation phenology improves timing and magnitude of stream DOC prediction in a forested watershed.…”
Section: Discussionmentioning
confidence: 97%
“…For example, Kim et al (2018) showed that accounting for inter‐annual phenology variation in a watershed model for Harvard Forest watershed in the north‐eastern United States improved predictions of ET/GPP and catchment discharge in both growing seasons and following dormant seasons. Accounting for climate‐dependent variable phenology will likely be more important under future climate conditions, as inter‐annual climate variability is expected to increase, accompanied by a shift in the seasonal pattern of vegetation phenology (Hayhoe et al, , Hwang et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation